DOST's DREAM project takes off - Valencia, George Robert III E.; Philippines. Department of Science and Technology
The article presents the DREAM project which is a component of DOST's Program NOAH. This is a 3D mapping program used to create flood models that will serve as basis to warn communities in advance of potentially deadly floods.
Keywords: Flood warning systems -- Philippines; Emergency communication systems -- Technological innovations; Natural disaster warning systems -- Technological innovations; DREAM Project; Disaster Risk and Exposure Assessment for Mitigation (DREAM).; LiDAR; Light Detection and Ranging; Program NOAH; Nationwide Operational Assessment of Hazards (NOAH).